Making sense of youth suicide : exploring young New Zealanders' views : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Psychology at Massey University, Wellington, New Zealand - Williams, Casey (Massey University, 2016)
Due to its sensitive nature, the suicide of young people can be a complex and difficult issue to address; yet it needs to be better understood in order to reduce the rate of young New Zealanders who die from suicide. While there has been a significant amount of research conducted on youth suicide, the aim of this research was to gain a deeper understanding of youth suicide within New Zealand by exploring why young people think their peers attempt, or die from, suicide. Six focus groups were held with 19 participants aged 16 to 24 years old. Discussions were transcribed and thematic analysis of the transcripts identified five themes and ten subthemes. These were: relationship factors (bullying and intimate relationships), internal factors (depressive disorders and coping skills), gender (kiwi masculinity and rates), external factors (alcohol and other drugs and circumstances), and support services (access and reluctance/barriers). The participants identified that youth suicide can be the result of a variety of factors, particularly noting the relationship between bullying (face to face or cyber-bullying) and suicide. It is recommended that a component which addresses youth suicide and provides young people with positive coping strategies is implemented into the New Zealand educational curriculum. It is anticipated that changes to the education curriculum, and by society challenging and changing common gender stereotypes, will help reduce youth suicide within New Zealand. Given that this research utilised a small sample size, where the majority of participants were female of European or Pakeha descent, future research with a larger more diverse sample would be beneficial.
Keywords: Youth; Suicide; Suicidal behaviour; New Zealand; Research Subject Categories::SOCIAL SCIENCES::Social sciences::Psychology